2020
DOI: 10.1093/ibd/izaa287
|View full text |Cite
|
Sign up to set email alerts
|

Double-Balloon Endoscopy in Crohn Disease: A Tertiary Referral Center Experience

Abstract: Background Crohn disease (CD) affects the small bowel in 80% of patients. Double balloon endoscopy (DBE) provides the potential for direct and extensive mucosal visualization with the potential for diagnostic monitoring and therapeutic intervention. This study aimed to investigate the safety and effectiveness of DBE in small-bowel CD. Methods From our DBE database, patients with CD at the time of index DBE (January 2004-Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 81 Another study reported that CD patients with SBS who underwent double-balloon endoscopy had an 80% surgery-free rate within 25 months after initial dilation. 86 Of note, the mean intervention-free period can extend to 54 months for CD patients with asymptomatic SBS who had strictures in ileocecal valve or had no elemental diets. 87 …”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“… 81 Another study reported that CD patients with SBS who underwent double-balloon endoscopy had an 80% surgery-free rate within 25 months after initial dilation. 86 Of note, the mean intervention-free period can extend to 54 months for CD patients with asymptomatic SBS who had strictures in ileocecal valve or had no elemental diets. 87 …”
Section: Search Strategymentioning
confidence: 99%
“…81 Another study reported that CD patients with SBS who underwent double-balloon endoscopy had an 80% surgery-free rate within 25 months after initial dilation. 86 Of note, the mean intervention-free period can extend to 54 months for CD patients with asymptomatic SBS who had strictures in ileocecal valve or had no elemental diets. 87 Since the recurrence rate of EBD is high up to 50% during follow-up, 88 a self-expandable metal stent with antimigration and removable features may be an alternative option.…”
Section: Treatment Of Intestinal Stricturesmentioning
confidence: 99%
“…However, EBD has a poor therapeutic effect on patients with CD and prestenotic luminal dilatation, which often indicates a long‐term disease or high‐grade stenosis 81,83‐85 . In 2020, several retrospective studies indicated that EBD using balloon‐assisted enteroscopy could delay the recurrence and reduce surgical intervention in patients with CD and small bowel stricture, with a short‐term clinical efficacy of 82.3% and long‐term effective rate of 76.5%, as well as a low complication rate of 5.3% 86‐88 …”
Section: Treatmentmentioning
confidence: 99%
“…In fact, it is not easy to stabilize the tip of the scope and to maintain a good visual field because of the limited space available, severe angulation, motility and adhesion in the small intestine. Nevertheless, the reported technical success rate is over 85% with a perforation rate of 1% [45,46].…”
Section: Treatment Of Intestinal Stricturesmentioning
confidence: 99%